PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, KOMPETENSI DAN RELIGIUSITAS TERHADAP KECURANGAN (FRAUD) APARATUR SIPIL NEGARA - M. Haykal Daditullah Indrapraja; Restu Agusti; Nanda Fito Mela (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
Fraud is a case that often occurs in various organizations. The goal of this research was to look into and assess organizational characteristics such as leadership style and organizational culture, as well as human factors such as organizational dedication and religiosity, in order to protect the State Civil Apparatus against fraud (ASN).The population in this study is the State Civil Apparatus (ASN) of the Riau Province Government as many as 15,455. Purposive sampling was utilized, with the requirements for ASN being in a post and working for more than two years. Questionnaires were collected by sending questionnaires directly and some were sending questionnaires in the form of a google form. A total of 104 civil servants participated in this study and 100 questionnaires were processed. The results of multiple regression analysis with the help of SPSS 27 show that organizational culture and competence have an effect on ASN fraud in the Riau Provincial Government. However, leadership style and religiosity have no effect on cheating. The results of this study have a contribution to the government in reducing the occurrence of fraud.